Pemetaan Permasalahan yang Dihadapi oleh Usaha Mikro Kecil Menengah (UMKM) di Kelurahan Tlogopatut dan Alternatif Solusinya - Jazilah, Fauzah Ainun; Ikaningtyas, Maharani (Jurnal Bisnis Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy.Tlogopatut subdistrict, like many other areas, has a number of MSMEs that face various challenges.This study aims to map the problems faced by MSMEs in Tlogopatut Village and present alternativesolutions that have the potential to improve their performance and business continuity. Throughsurveys, interviews and data analysis, we identified several main problems which include poor digitalmarketing management, lack of awareness among MSME players regarding the importance ofbusiness legality, and the absence of business legality owned by some MSMEs in the Tlogopatut subdistrict. As an alternative solution, we propose a training and mentoring program for MSME owners,and a more effective marketing strategy through the use of digital technology. It is hoped that theresults of this research can help MSMEs in Tlogopatut Village to overcome their problems andencourage local economic growth.Keywords: MSME; Digital Marketing; Business Legallity